Disruptions in cortical circuit connectivity distinguish widespread hyperalgesia from localized pain - Kenefati, George; Rockholt, Mika M.; Eisert, Katherine; Zhang, Qiaosheng; Ok, Deborah; Gharibo, Christopher G.; Voiculescu, Lucia Daiana; Doan, Lisa V.; Chen, Zhe Sage; Wang, Jing (Frontiers in Pain Research, 2025)
IntroductionThis study aims to investigate the interregional functional connectivity in chronic back pain patients with widespread hyperalgesia, patients with localized back pain, and pain-free controls using stimulus-evoked high-density EEG recordings.MethodsWe conducted high-density EEG recordings to compare the functional connectivity and betweenness centrality between these groups.ResultsCompared with controls, chronic pain patients showed altered functional connectivity between regions that process cognitive information and regions that process sensory or affective information. Widespread hyperalgesia, however, is further differentiated from localized pain by decreased inter-hemispheric connectivity of sensory and affective areas and increased intra-hemispheric connectivity between sensory and cognitive cortices. Graph-theoretic analysis showed that whereas chronic pain is associated with decreased centrality of prefrontal, orbitofrontal, and cingulate areas, widespread hyperalgesia is distinguished by increased centrality of prefrontal and insular areas.DiscussionTogether, our results show that although widespread hyperalgesia shares certain features with localized pain, it is further characterized by distinct cortical mechanisms.